Cardiovascular outcome of pediatric patients with bi-allelic (homozygous) familial hypercholesterolemia before and after initiation of multimodal lipid lowering therapy including lipoprotein apheresis - Taylan, Christina; Driemeyer, Joenna; Schmitt, Claus P.; Pape, Lars; Büscher, Rainer; Galiano, Matthias; König, Jens; Schürfeld, Carsten; Spitthöver, Ralf; Versen, Axel; Koziolek, Michael; Marsen, Tobias A.; et al. (The American journal of cardiology, 2020)
Twenty-four patients with bi-allelic familial hypercholesterolemia commencing chronic lipoprotein apheresis (LA) at a mean age of 8.5 ± 3.1 years were analysed retrospectively and in part prospectively with a mean follow-up of 17.2 ± 5.6 years. Mean age at diagnosis was 6.3 ± 3.4 years. Untreated mean LDL-C concentrations were 752 mg/dl ± 193 mg/dl (19.5 mmol/l ± 5.0 mmol/l). Multimodal lipid lowering therapy including LA resulted in a mean LDL-C concentration of 184 mg/dl (4.8 mmol/l), which represents a 75.5% mean reduction. Proprotein convertase subtilisin/kexin type 9-antibodies contributed in 3 patients to LDL-C lowering with 5 patients remaining to be tested. After commencing chronic LA, 16 patients (67%) remained clinically stable with only subclinical findings of atherosclerotic cardiovascular disease (ASCVD), and neither cardiovascular events, nor need for vascular interventions or surgery. In 19 patients (79%), pathologic findings were detected at the aortic valve (AV), which in the majority were mild. AV replacement was required in 2 patients. Mean Lipoprotein(a) concentration was 42.4 mg/dl, 38% had >50 mg/dl. There was no overt correlation of AV pathologies with other ASCVD complications, or Lipoprotein(a) concentration. Physicochemical elimination of LDL particles by LA appears indispensable for patients with bi-allelic familial hypercholesterolemia and severe hypercholesterolemia to maximize the reduction of LDL-C. In conclusion, in this rare patient group regular assessment of both the AV, as well as all arteries accessible by ultrasound should be performed to adjust the intensity of multimodal lipid lowering therapy with the goal to prevent ASCVD events and aortic surgery.